Application of video data classification models using convolutional neural networks - Tvoroshenko, I.; Pomazan, V.; Gorokhovatskyi, V.; Kobylin, O. (International Journal of Academic and Applied Research, 2023)
This paper explores the classification of video data with convolutional neural networks. It discusses how convolutional neural network architecture can do this task with fastness and maximum efficiency. By analyzing the different convolutional neural network models model was proposed that showed great results in this video classification task. The strengths and weaknesses of the neural network model for video classification have been identified, and the prospects for further work have also been outlined.
Keywords: artificial intelligence; classification; convolutional neural networks (CNN); neural network; video classification